(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
In light of the escalating global challenges, the exploration of unconventional edible wild plants gains significance. This study focuses on Calotropis procera, renowned for its medicinal and toxic properties, particularly in its leaves and fruits. Analysis of these plant parts, following the Association of Official Analytical Chemists’ procedures, revealed nutritional and phytochemical compositions (dry weight). Proximate composition (%) of leaves and fruits were: Moisture (9.03, 8.37), crude protein (20.81, 19.55), crude fiber (10.20, 20.91), crude fat (3.58, 3.41), ash (17.21, 16.83), and carbohydrate (39.19, 31.04), respectively. The predominant phytochemical was phytate with values of 116.5 and 83.72 (mg/100g) for leaves and fruits. Amino acid analysis revealed total contents of 72.43 and 70.82 g/100g crude protein for leaves and fruits, with the highest concentration in both being Glu (9.45 and 9.39 g/100g cp). Essential amino acids (with His) were 38.14 g/100g cp (52.67%) for leaves and 36.81 g/100g cp (51.98%) for fruits. While these findings highlight their potential as dietary supplements, further research is essential to develop processing methods that mitigate risks. This study contributes to understanding the nutritional and ant-nutritional profile of Sodom apple, emphasizing the importance of a balanced approach to harness its benefits effectively.